Conditioned Medium from H2O2-Preconditioned Human Adipose-Derived Stem Cells Ameliorates UVB-Induced Damage to Human Dermal Fibroblasts - María Burón; Teodoro Palomares; Patricia Garrido-Pascual; Borja Herrero de la Parte; Ignacio García-Alonso; Ana Alonso-Varona (MDPI AG, 2022)
Human skin exposure to ultraviolet B (UVB) radiation can result in acute photodamage through oxidative modifications of cellular components and biomolecules involved in the metabolism of dermal cells. Recently, the therapeutic potential of human adipose-derived stem cells (hASCs) has been investigated as a novel strategy for photoprotection due to their pro-angiogenic properties, protective activity against oxidative stress and paracrine effect on dermal cells. To enhance these therapeutic properties, hASCs can be preconditioned by exposing them to sublethal cellular stressors. In this study, we first analyzed response capacity against UVB-induced oxidative stress in H2O2-preconditioned hASCs (called HC016 cells); and second, we evaluated the photoprotective effect of HC016-conditioned medium (CM) in an in vitro UVB irradiation model in cultured human foreskin fibroblasts (hFFs). The results demonstrated that HC016 cells have a greater capacity to respond efficiently to UVB-induced oxidative stress, evidenced by higher Nrf2 antioxidant system activity and enhanced viability and migration capacity. Further, HC016-CM treatment increased viability, migratory capacity and collagen type I synthesis in hFFs exposed to UVB radiation, as well as reducing their cytotoxicity, apoptosis, senescence and IL-6 secretion. Collectively, these findings support the view that HC016 cells could protect against UVB-induced photodamage via paracrine mechanisms.